1977
DOI: 10.1073/pnas.74.11.4914
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase binding sites in λp lac 5 DNA

Abstract: The in vitro binding of the Escherichia coli RNA polymerase (nucleosidetriphosphate:RNA nucleotidyltransferase; EC 2.7.7.6) to fragments of Aplc5 DNA generated by restriction endonucleases HindII and HindIII has been studied by a filter binding technique. The results are consistent with RNA polymerase binding at p-, the INT promoter (pI), several sites in the b2 region, the mis promoter, the oop promoter (or po), and pro. Binding was also observed on some fragments that are not known to contain active promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 28 publications
5
14
0
Order By: Relevance
“…The denaturation map shown in figure 6 reveals that the bi-directional TET operator-promoter system consisting of two overlapping promoters and possibly two operators [18] is the most unstable part of the 1450-bp sequence. This result agrees well with the notion that promoters tend to occur in AT rich regions of genomic DNA [3,4,201. It is well established that E. coli RNA polymerase unwinds about ten base pairs upstream of the mRNA start nucleotide upon binding to a promoter [51.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The denaturation map shown in figure 6 reveals that the bi-directional TET operator-promoter system consisting of two overlapping promoters and possibly two operators [18] is the most unstable part of the 1450-bp sequence. This result agrees well with the notion that promoters tend to occur in AT rich regions of genomic DNA [3,4,201. It is well established that E. coli RNA polymerase unwinds about ten base pairs upstream of the mRNA start nucleotide upon binding to a promoter [51.…”
Section: Discussionsupporting
confidence: 92%
“…It was noted previously that promotors tend to occur in AT rich regions of the genomic DNA [3,4] which is consistent with the ability of RNA polymerase to unwind about ten base pairs in order to allow the synthesis of a mRNA from the DNA template (5].…”
supporting
confidence: 76%
“…On the other hand, it has been reported that closed and open complexes are formed in sites that are unproductive for transcription. 33 The resulting scores for the 116 promoters in the training set were rather variable, covering a sevenfold range (1.4 -10.07), being contained within m^3s (see column two in Table 2). The observation described in Figure 3(b) means that the strategy of searching, based on selecting the highest scoring signal, fails in more than 50% of the cases.…”
Section: Re-evaluating the Computational Model Of A Promotermentioning
confidence: 99%
“…The P2 promoter region of pBR322 is in one of the two regions of high A T density in this plasmid as is the P3 promoter, and thus, ÁInsA-B HInsB may have acted on the P2 promoter region. A T-richness is characteristic of RNA polymerase binding sites (Jones et al, 1977;Nakamura & Inoue, 1979), and apparently re¯ects a need for denaturing DNA during transcription initiation. Perhaps IS1 transposition is also facilitated by denaturability of the target site DNA as described by Galas et al (1980).…”
Section: Discussionmentioning
confidence: 99%